Potentiating Effect of Glabridin on GABAA Receptor-Mediated Responses in Dorsal Raphe Neurons - Jin, Zhenhua; Kim, Sojin; Cho, Suengmok; Kim, In-Ho; Han, Daeseok; Jin, Young-Ho (Planta Medica, 2013)
Flavonoid-rich ethanol extracts of licorice root have sedative and anxiolytic effects. Glabridin is a major flavonoid component from licorice which we evaluated by examining GABA responses in acutely isolated dorsal raphe neurons of the rat. Neurons were recorded with patch-clamp methods at a holding potential of − 50 mV. Glabridin potentiated GABA-induced responses by positively modulating GABAA receptor responses with different concentration range. GABA (2 × 10−6 M)-evoked currents were potentiated in a stepwise pattern increasing glabridin concentration. Between 10−12 and 10−8 M glabridin increased GABA responses by about 140 % of the control. At concentrations above 10− 7 M, a much larger, dose-dependent potentiation occurred before reaching a plateau at 3 × 10−6 M glabridin. A hypnotic drug, zolpidem, also induced biphasic concentration-potentiation relationship. The glabridin potentiation ratio was 2.2 times larger than the maximum potentiation to the benzodiazepine receptor full agonist diazepam. Benzodiazepine receptor antagonist, flumazenil (3 × 10−7 M), failed to inhibit glabridin (3 × 10−7 M)-induced potentiation. This result implies that glabridin may exhibit sedative and hypnotic effects by potentiating GABAergic inhibition in dorsal raphe neurons by GABAA receptor actions.
Keywords: licorice; flavonoid; benzodiazepine receptor; flumazenil; sedative-hypnotic activity; GABAA receptor; Glycyrrhiza glabra; Fabaceae